2021
DOI: 10.1111/jcpe.13518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of xenogeneic collagen matrix versus free gingival grafts for keratinized mucosa augmentation around dental implants: A randomized controlled clinical trial

Abstract: Aim: To evaluate the outcomes of an apically repositioned flap (ARF) plus xenogeneic collagen matrix (XCM) in augmenting keratinized mucosa width (KMW) around dental implants when compared with ARF plus free gingival grafts (FGG).Materials and methods: Twenty-six participants with at least one site with KMW ≤2 mm were randomized into FGG or XCM group. Clinical examinations were performed at baseline and at 2 and 6 months after surgery, including KMW, keratinized mucosa thickness, gingival index (GI), and probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(84 citation statements)
references
References 36 publications
2
34
0
2
Order By: Relevance
“…The free gingival graft will help in the prevention of further recession [ 20 ]. Lesser invasive procedures like the use of collagen matrix-like Geistlich Mucograft® (Geistlich Pharma AG, Wolhusen, Switzerland) and Mucoderm® (botiss medical AG, Berlin, Germany) can be used as an alternative to autogenous grafts like free gingival grafts for the treatment of such similar scenarios [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The free gingival graft will help in the prevention of further recession [ 20 ]. Lesser invasive procedures like the use of collagen matrix-like Geistlich Mucograft® (Geistlich Pharma AG, Wolhusen, Switzerland) and Mucoderm® (botiss medical AG, Berlin, Germany) can be used as an alternative to autogenous grafts like free gingival grafts for the treatment of such similar scenarios [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vellis et al found that CM (gain 4.4 mm) achieved comparable results to FGG (gain 4.6 mm), and the two approaches do not affect probing depth, marginal recession and bleeding on probing [40]. Huang et al showed that FGG (gain 4.1 mm) could result in greater increase of KMW than CM (gain 1.7 mm), though both could increase KMW, maintain peri-implant health, and attain comparable aesthetic outcomes [41]. Fu et al reported at 6 months, the KMW was signi cantly higher with FGG (3.74 mm at 6 months) than with CM (2.82 mm at 6 months) in the posterior mandible [42].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 93 studies (76.9%) described PMC using esthetic indices with predetermined grading scores. [16][17][18][31][32][33][34][35][36]38,39,[42][43][44][45][46][47][48][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][70][71][72][73][74][75][76][77][80][81][82][84][85][86][87][88][89][90][91][92][93]…”
Section: Methods For Assessing Pmcmentioning
confidence: 99%
“…tissue dehiscence coverage esthetic score (IDES). 18 One study utilized a modified gingival index, 30 one article followed a 3-point scoring system (0 for obvious color differences, 1 for moderate difference and 2 for a natural color/no differences) 68 and one study mentioned a 0-2 point grading for PMC, without specifying the criteria for this evaluation 89 (Tables S10 of the Appendix and 1).…”
Section: Pmc Assessment Using Esthetic Indicesmentioning
confidence: 99%